2018
DOI: 10.1007/s10646-018-1965-x
|View full text |Cite
|
Sign up to set email alerts
|

Extrapolation of imidacloprid toxicity between soils by exposing Folsomia candida in soil pore water

Abstract: Soil properties like organic matter (OM) content show great variation, making it hard to predict the fate and effects of a chemical in different soils. We therefore addressed the question: can we remove the complexity of the soil matrix and yet accurately predict soil toxicity from porewater exposures? Folsomia candida was exposed to imidacloprid in natural (LUFA 2.2 [4.02% OM], Grassland [12.6% OM]) and artificial soils (OECD 5 [6.61% OM], OECD 10 [10.8% OM]), in pore water extracted from spiked LUFA 2.2 soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…This was, for instance, also shown for copper uptake effects on springtails by Bruus Pedersen et al (2000). Soil porewater absorption through the cuticle and ventral tube is a major route of imidacloprid exposure, and Ogungbemi and van Gestel (2018) have shown that exposure through porewater can closely resemble the exposure scenarios in soil.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was, for instance, also shown for copper uptake effects on springtails by Bruus Pedersen et al (2000). Soil porewater absorption through the cuticle and ventral tube is a major route of imidacloprid exposure, and Ogungbemi and van Gestel (2018) have shown that exposure through porewater can closely resemble the exposure scenarios in soil.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms can drive this phenomenon. Firstly, the collembolans suffer from disoriented movements and spasms owing to the neurotoxic effects of imidacloprid (Ogungbemi and van Gestel 2018). This might lead to uncontrolled loss of energy, which reduces the resources available for reproduction (Anderson and Harmon-Threatt 2019) or altered sexual behavior (Haynes 1988).…”
Section: Temporary Cessation Of Egg Layingmentioning
confidence: 99%
See 1 more Smart Citation
“…These pesticides are widely used for different crops, as the tomato one, which is quite common in Mediterranean countries. Despite the relevance of these pesticides for the economy, their impact on the biotic cannot be neglected ,. The screening strategy proposed in the present study resorts to MD simulations, which allows for a detailed investigation about the main interactions that promote the formation of the oligomer‐pesticide complex.…”
Section: Introductionmentioning
confidence: 99%
“…(2014) and the PBMC (2014), for 90% of Brazilian biomes, reductions in precipitation regimes by 5–20% are expected by 2040, 20–35% between the years 2041 to 2070, and 30–50% from 2071 to 2100. Reductions in soil moisture are also expected (Dai, 2013) that can negatively affect the habitat of edaphic organisms, which play crucial roles in cycling nutrients, decomposition of organic matter, maintenance of soil structure, permeability, and gas exchange (Edwards, Arancon, Vasko‐Bennett, Little, & Askar, 2008; Ogungbemi & Van Gestel, 2018; Phelan et al., 2016).…”
Section: Introductionmentioning
confidence: 99%